Analisis Pembiayaan Pengelolaan Sampah Perdesaan Jawa Barat - Yudha Hadian Nur; David Sutasurya; Arief Dhany Sutadian; Ricky Alamsyah; Muthya Diana; Anita Vitriana; Isma Hanifa Ma’ruf; Saniar Rabithoh Wijaya; Windi Indranoviyanti (School of Postgraduate Studies, Diponegoro Univer, 2023)
Rural development is an important part of national development considering that 82% of Indonesia's territory is rural. The rural waste management has not received the same attention as those in urban areas. This can be seen from the high gap between urban and rural areas, which is also found in West Java Province. Through this study, nine waste management scenarios of rural areas for a 20 year planning (S1-S9), which were divided based on rural and peri-urban, has been developed. The aim of the study was to find the best model of rural waste management from a financial perspective that can be applied in West Java, especially in the rural’s Citarum watershed area. Analysis on the financial provided two types of costs, namely capital expenditures (CAPEX) and operational expenditures (OPEX) in rupiah per ton. The results of the study showed that home composting (S9) for both peri-urban and rural areas is the most efficient. Meanwhile, the mixed-based scenario with landfill-based residue handling (S2) in both peri-urban and rural areas was the one that requires the highest cost. The accumulation of waste management costs was dominated OPEX, so an investment policy with a long-term perspective is needed to reduce that OPEX.